Hubungan Power Tungkai Dan Power Lengan Terhadap Jumping Smash Siswa Ekstrakulikuler Badminton Ma Nurul Falah - Ziqri Yahandi; Widati Amalin Ulfah; Ivandi Rahman; Chopa Renaldi; Artha Yuranda; Muhammad Irfan Saputra (JURNAL STAMINA, 2022)
This study aims to determine the contribution of leg power and arm power to jumping smash in badminton extracurricular students at MA Nurul Falah Airmesu Timur. The problem in this study is "Does leg power and arm power have a contribution to badminton jumping smash in badminton extracurricular students at MA Nurul Falah Airmesu Timur?" The population of this study were all badminton extracurricular students at MA Nurul Falah Airmesu Timur, totaling 17 students. Total sampling technique is the technique used for sampling in this study (ie the technique of determining the sample if the entire population is sampled) with a total of 17 badminton extracurricular students at MA Nurul Falah. The variables of this study consisted of leg power, arm power, and jumping smash.